White toner for developing electrostatic images
By employing an amorphous polyester resin and titanium oxide coated with a specific addition polymer, the white toner achieves enhanced dispersibility and hiding power, overcoming previous toner limitations in image formation and fixing properties.
Patent Information
- Application Number
- JP2021123395
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-30
- Filing Date
- 2021-07-28
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-07-28
AI Technical Summary
Existing white toners face challenges in achieving high hiding power due to poor dispersibility of titanium oxide, leading to insufficient hiding power and potential deterioration of low-temperature fixing properties.
The use of an amorphous polyester resin as a binder and titanium oxide coated with a specific addition polymer, incorporating an anionic group and polyalkylene oxide group, improves dispersibility and chargeability, enhancing hiding power and low-temperature fixing properties.
The solution results in a white toner capable of forming images with high concealing properties and improved low-temperature fixing ability, addressing the limitations of previous toners.
Smart Images

Figure 0007670572000001 
Figure 0007670572000002 
Figure 0007670572000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a white toner for developing electrostatic images, which is used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like. [Background technology]
[0002] As print media become more diverse, there is a growing demand for electrophotographic printing on print media other than paper. One of the main media is polypropylene film (hereinafter also referred to as "PP film") and polyethylene film (hereinafter also referred to as "PE film"), which are used for PET bottle labels and various packages. In addition, there is an increasing demand for printing on recording media such as colored paper and resin film, which are not white, rather than the conventional printing on white paper. When printing on recording media that are not white, a white toner is used for the purpose of expressing whiteness and for the purpose of improving visibility. Titanium oxide, which is an inorganic pigment with high hiding power, is commonly used as a colorant for white toner.
[0003] Patent Document 1 describes a white toner for developing electrostatic images, which contains a colorant and a binder resin consisting of a crystalline resin and a non-crystalline resin, with the aim of obtaining a toner for developing electrostatic images that is less likely to cause image defects and has high density and high concealing properties, and is characterized in that the content of the crystalline resin in the toner is 5 to 25 mass % and the content of the colorant in the toner is 15 to 40 mass %. Patent Document 2 describes a white toner having excellent hiding power and low-temperature fixing power, which contains toner particles having a resin, a compound A, and a white pigment, and is characterized in that when the refractive index of the resin is n1, the refractive index of the compound A is n2, and the refractive index of the white pigment is n3, these satisfy a specific relational formula, the compound A forms domains in the toner particles within the matrix of the resin, and the white pigment is present in the domains. Furthermore, Patent Document 3 describes a white toner for developing electrostatic images, which has toner particles containing a binder resin including at least a crystalline polyester resin and an amorphous polyester resin, and a white pigment, for the purpose of suppressing light transmission through a white image, and which has a loss tangent tanδ of 0.2 or more and 1.0 or less at 30°C as measured by dynamic viscoelasticity measurement. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2007-33719 A [Patent Document 2] JP 2020-148992 A [Patent Document 3] JP 2019-113686 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the white toner described in Patent Document 1, by incorporating a large amount of white pigment in the resin, it is possible to improve the hiding power to some extent, but by incorporating a large amount of white pigment, the white pigment tends to become poorly dispersed, and there is a limit to how much the hiding power can be improved by simply increasing the content of the white pigment. Furthermore, in the white toners described in Patent Documents 2 and 3, the titanium oxide was not uniformly incorporated or dispersed in the toner, and the hiding power was insufficient. The present invention relates to a white toner for developing electrostatic images, which is capable of forming a white image with high concealing properties. A toner capable of forming an image with high hiding power is also called a toner with excellent hiding power. [Means for solving the problem]
[0006] The present inventors have found that by using an amorphous polyester resin as a binder resin, using titanium oxide coated with a specific polymer as a colorant, and having the titanium oxide have a specific average primary particle size, a white toner for developing electrostatic images capable of forming images with high concealing properties can be obtained. The present invention relates to the following [1]. [1] A white toner for developing electrostatic images, comprising a binder resin and a colorant, The binder resin contains an amorphous polyester resin, the colorant is titanium oxide coated with an addition polymer of raw material monomers including an addition polymerizable monomer having an anionic group and an addition polymerizable monomer having a polyalkylene oxide group; White toner for developing electrostatic images. Effect of the Invention
[0007] According to the present invention, there is provided a white toner for developing electrostatic images, which is capable of forming images with high hiding power. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] [White toner for developing electrostatic images] The white toner for developing electrostatic images of the present invention (hereinafter, also simply referred to as "toner") contains a binder resin and a colorant, the binder resin contains an amorphous polyester resin, and the colorant is titanium oxide coated with an addition polymer of raw material monomers including an addition polymerizable monomer having an anionic group and an addition polymerizable monomer having a polyalkylene oxide group. The white toner for developing electrostatic images of the present invention can form images with high concealing properties.
[0009] In order to obtain a toner with high hiding power, it is necessary to blend a large amount of white pigment into the toner. However, in the case of chemical toners produced by the aggregation fusion method (emulsion polymerization method, aggregation coalescence method), the toner is produced using a white pigment dispersion dispersed in water, but if the dispersibility is insufficient, it is difficult to incorporate the white pigment uniformly into the toner, resulting in a decrease in hiding power. Also, in the case of pulverized toners, if a large amount of white pigment is blended, the white pigment cannot be highly dispersed during the kneading of the raw materials, resulting in a decrease in hiding power. Therefore, in this application, it has been discovered that by coating the white pigment titanium oxide with a specific addition polymer, the dispersibility of the white pigment dispersion in water in chemical toners can be improved, and further, by using a white pigment coated with this polymer in chemical toners and pulverized toners, the dispersibility of the white pigment in the toners can be improved. It is believed that the improvement in dispersibility of titanium oxide, which is a white pigment, in water is due to charge repulsion by the anionic group of the addition polymer and steric repulsion by the polyalkylene oxide group, which stably disperses titanium oxide in water. Also, in the toner, since titanium oxide is covered with the addition polymer, the polyalkylene oxide group of the addition polymer adsorbed on the hydrophilic titanium oxide surface suppresses the aggregation of titanium oxide in the toner, which is believed to improve the dispersibility of titanium oxide in the toner. It is believed that this improves the hiding power. In addition, in toners for developing electrostatic images that contain a large amount of white pigment, the low-temperature fixing property may be deteriorated, possibly because the toner becomes highly viscoelastic due to the local filler effect of aggregated pigment. In the present invention, the dispersibility of titanium oxide, which is a white pigment, in the toner is improved, which suppresses the local filler effect of the white pigment and suppresses the toner from becoming highly elastic, and is therefore considered to have contributed to the improvement of low-temperature fixing property as an additional effect. Furthermore, as a result of improving the dispersibility of titanium oxide in toner particles, this can also contribute to improving the chargeability as an additional effect. The above-mentioned mechanism regarding the effect of the present invention is merely a presumption, and the present invention is not limited thereto.
[0010] The definitions of various terms used in this specification are given below. Whether a resin is crystalline or amorphous is determined by the crystallinity index. The crystallinity index is defined as the ratio of the softening point of the resin to the temperature of the maximum endothermic peak (softening point (°C) / maximum endothermic peak temperature (°C)) in the measurement method described in the examples below. A crystalline resin is one with a crystallinity index of 0.6 or more and 1.4 or less. An amorphous resin is one in which no endothermic peak is observed, or, if observed, has a crystallinity index of less than 0.6 or more than 1.4. The crystallinity index can be appropriately adjusted by the types and ratios of raw material monomers, as well as production conditions such as reaction temperature, reaction time, and cooling rate. With respect to hydrocarbon groups, the references "(iso or tertiary)" and "(iso)" in parentheses refer to both the cases with and without the prefixes present; the absence of the prefixes indicates normal. "(Meth)acrylic acid" means at least one selected from acrylic acid and methacrylic acid. "(Meth)acrylate" means at least one selected from acrylate and methacrylate. The "(meth)acryloyl group" means at least one selected from an acryloyl group and a methacryloyl group. The term "toner particles" refers to toner base particles excluding external additives from the toner.
[0011] [Binder Resin] In this embodiment, from the viewpoint of obtaining a toner with excellent hiding power, the binder resin preferably contains an amorphous polyester resin (hereinafter also referred to as amorphous polyester resin A), and from the viewpoint of hiding power and low-temperature fixability, the binder resin preferably contains a crystalline polyester resin (hereinafter also referred to as crystalline polyester resin C) in addition to the amorphous polyester resin.
[0012] (Amorphous polyester resin A) The amorphous polyester resin A is, for example, an amorphous polyester resin containing a polycondensate of an alcohol component and a carboxylic acid component. Examples of the amorphous polyester resin include polyester resin and modified polyester resin. Examples of the modified polyester resin include urethane modified polyester resin, epoxy modified polyester resin, and composite resin containing polyester resin segment and addition polymerization resin segment. Among these, it is preferable to include amorphous composite resin A containing polyester resin segment which is a polycondensation product of alcohol component and carboxylic acid component, and addition polymerization resin segment which is an addition polymerization product of raw material monomer containing styrene compound. In addition to amorphous composite resin A, it is preferable to contain amorphous polyester resin B containing polycondensation product of alcohol component and carboxylic acid component as amorphous polyester resin.
[0013] <Amorphous composite resin A> From the viewpoint of obtaining a toner having excellent hiding power, the amorphous composite resin A (hereinafter, also simply referred to as "composite resin A") preferably contains a polyester resin segment, an addition polymerization resin segment which is an addition polymerization product of raw material monomers including a styrene-based compound, and a structural unit derived from a bireactive monomer bonded to the polyester resin segment and the addition polymerization resin segment via a covalent bond. From the viewpoint of further improving the hiding power, the composite resin A preferably further contains a structural unit derived from a hydrocarbon wax having at least one of a carboxy group and a hydroxyl group (hereinafter also referred to as "hydrocarbon wax WA").
[0014] The polyester resin segment is composed of a polycondensate of an alcohol component and a carboxylic acid component. Examples of the alcohol component include aromatic diols, alkylene oxide adducts of aromatic diols, linear or branched aliphatic diols, alicyclic diols, and trihydric or higher polyhydric alcohols. Among these, alkylene oxide adducts of aromatic diols are preferred. The alkylene oxide adduct of an aromatic diol is preferably an alkylene oxide adduct of bisphenol A, more preferably an alkylene oxide adduct of formula (I):
[0015] [ka] (In the formula, OR 1 and R 2 O is an oxyalkylene group, and R 1 and R 2 each independently represents an ethylene group or a propylene group, x and y represent the average number of moles of alkylene oxide added and are each positive numbers, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, and more preferably 4 or less.
[0016] Examples of the alkylene oxide adduct of bisphenol A include a propylene oxide adduct of bisphenol A [2,2-bis(4-hydroxyphenyl)propane] and an ethylene oxide adduct of bisphenol A. These may be used alone or in combination. Among these, the propylene oxide adduct of bisphenol A is preferred. The content of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 70 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and is 100 mol % or less, even more preferably 100 mol %.
[0017] Examples of linear or branched aliphatic diols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2,2-dimethyl-1,3-propanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol. Examples of alicyclic diols include hydrogenated bisphenol A [2,2-bis(4-hydroxycyclohexyl)propane] and adducts of hydrogenated bisphenol A with alkylene oxides having 2 to 4 carbon atoms (average number of moles added: 2 to 12). Examples of trihydric or higher polyhydric alcohols include glycerin, pentaerythritol, trimethylolpropane, and sorbitol. These alcohol components may be used alone or in combination of two or more.
[0018] Examples of the carboxylic acid component include dicarboxylic acids and polycarboxylic acids having three or more carboxylic acids. Examples of dicarboxylic acids include aromatic dicarboxylic acids, linear or branched aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids. Among these, at least one selected from aromatic dicarboxylic acids and linear or branched aliphatic dicarboxylic acids is preferred. Examples of aromatic dicarboxylic acids include phthalic acid, isophthalic acid, and terephthalic acid. Among these, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred. The amount of aromatic dicarboxylic acid in the carboxylic acid component is preferably 20 mol% or more, more preferably 30 mol% or more, even more preferably 40 mol% or more, even more preferably 45 mol% or more, and is preferably 90 mol% or less, more preferably 80 mol% or less, even more preferably 75 mol% or less.
[0019] The linear or branched aliphatic dicarboxylic acid preferably has 2 or more, more preferably 3 or more, and preferably has 30 or less, more preferably 20 or less. Examples of linear or branched aliphatic dicarboxylic acids include oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, dodecanedioic acid, azelaic acid, and succinic acid substituted with a hydrocarbon group having 1 to 20 carbon atoms. Examples of succinic acid substituted with a hydrocarbon group having 1 to 20 carbon atoms include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. Among these, fumaric acid and sebacic acid are preferred. The amount of linear or branched aliphatic dicarboxylic acid in the carboxylic acid component is preferably 1 mol % or more, more preferably 10 mol % or more, even more preferably 15 mol % or more, and is preferably 70 mol % or less, more preferably 60 mol % or less, even more preferably 50 mol % or less.
[0020] The trivalent or higher polyvalent carboxylic acid is preferably a trivalent carboxylic acid, such as trimellitic acid. When a trivalent or higher polycarboxylic acid is contained, the amount of the trivalent or higher polycarboxylic acid in the carboxylic acid component is preferably 3 mol% or more, more preferably 5 mol% or more, even more preferably 8 mol% or more, and is preferably 30 mol% or less, more preferably 20 mol% or less, even more preferably 15 mol% or less. These carboxylic acid components may be used alone or in combination of two or more.
[0021] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0022] The addition polymerized resin segment is an addition polymer of raw material monomers containing a styrene-based compound, from the viewpoint of obtaining a toner exhibiting high hiding power. The styrene-based compound may be unsubstituted or substituted styrene. Examples of the substituent on styrene include an alkyl group having 1 to 5 carbon atoms, a halogen atom, an alkoxy group having 1 to 5 carbon atoms, a sulfo group, or a salt thereof. Examples of styrene-based compounds include styrene, methylstyrene, α-methylstyrene, β-methylstyrene, tert-butylstyrene, chlorostyrene, chloromethylstyrene, methoxystyrene, styrenesulfonic acid, and salts thereof. Among these, styrene is preferred. The content of the styrene-based compound in the raw material monomers of the addition polymerization resin segment is preferably 50% by mass or more, more preferably 65% by mass or more, even more preferably 70% by mass or more, and is 100% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less.
[0023] Examples of raw material monomers other than styrene-based compounds include (meth)acrylic acid esters such as alkyl (meth)acrylate, benzyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; olefins such as ethylene, propylene, and butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as vinyl methyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone. Among these, (meth)acrylic acid esters are preferred, and alkyl (meth)acrylates are more preferred. From the viewpoint of obtaining better hiding power, the number of carbon atoms in the alkyl group in the alkyl (meth)acrylate is preferably 1 or more, more preferably 4 or more, even more preferably 6 or more, and is preferably 24 or less, more preferably 22 or less, even more preferably 20 or less. Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, (iso)propyl (meth)acrylate, (iso or tertiary)butyl (meth)acrylate, (iso)amyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (iso)octyl (meth)acrylate, (iso)decyl (meth)acrylate, (iso)dodecyl (meth)acrylate, (iso)palmityl (meth)acrylate, (iso)stearyl (meth)acrylate, and (iso)behenyl (meth)acrylate. Among these, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and stearyl (meth)acrylate are preferred, and stearyl (meth)acrylate is more preferred.
[0024] In the raw material monomers of the addition polymerization resin segment, the content of the (meth)acrylic acid ester is preferably 5 mass% or more, more preferably 10 mass% or more, even more preferably 15 mass% or more, and preferably 50 mass% or less, more preferably 40 mass% or less, even more preferably 30 mass% or less.
[0025] The total amount of the styrene-based compound and the (meth)acrylic acid ester in the raw material monomers of the addition polymerization resin segment is preferably 80 mass % or more, more preferably 90 mass % or more, even more preferably 95 mass % or more, and even more preferably 100 mass %.
[0026] The composite resin A has a constitutional unit derived from a bireactive monomer bonded to a polyester resin segment and an addition polymerization resin segment via a covalent bond. The term "structural unit derived from a bireactive monomer" refers to a unit formed by reaction of the functional group and the unsaturated bond site of a bireactive monomer. Examples of the bireactive monomer include addition polymerizable monomers having at least one functional group selected from a hydroxyl group, a carboxyl group, an epoxy group, a primary amino group, and a secondary amino group in the molecule. Among these, from the viewpoint of reactivity, addition polymerizable monomers having at least one functional group selected from a hydroxyl group and a carboxyl group are preferred, and addition polymerizable monomers having a carboxyl group are more preferred. Examples of the addition polymerizable monomer having a carboxy group include acrylic acid, methacrylic acid, fumaric acid, and maleic acid. Among these, from the viewpoint of reactivity in both the polycondensation reaction and the addition polymerization reaction, acrylic acid and methacrylic acid are preferred, and acrylic acid is more preferred. The amount of the constitutional units derived from the bireactive monomer is preferably 1 mol part or more, more preferably 5 mol parts or more, even more preferably 10 mol parts or more, and is preferably 30 mol parts or less, more preferably 25 mol parts or less, even more preferably 20 mol parts or less, relative to 100 mol parts of the alcohol component of the polyester resin segment of the composite resin A.
[0027] The component derived from the hydrocarbon wax WA is, for example, the hydrocarbon wax WA in which a hydroxyl group or a carboxyl group has reacted and is covalently bonded to a polyester resin segment. The hydrocarbon wax WA has at least one of a carboxy group and a hydroxyl group. The hydrocarbon wax WA may have either a hydroxyl group or a carboxy group, or both, but preferably has a hydroxyl group and a carboxy group from the viewpoint of improving hiding power. The hydrocarbon wax WA can be obtained, for example, by modifying an unmodified hydrocarbon wax by a known method. Examples of raw materials for the hydrocarbon wax WA include paraffin wax, Fischer-Tropsch wax, microcrystalline wax, polyethylene wax, and polypropylene wax. Among these, paraffin wax and Fischer-Tropsch wax are preferred.
[0028] Commercially available examples of hydrocarbon waxes having hydroxyl groups include "Unilin 700," "Unilin 425," and "Unilin 550" (all manufactured by Baker Petrolite).
[0029] An example of a commercially available product of a hydrocarbon wax having a carboxy group is maleic anhydride modified ethylene-propylene copolymer "HIWAX 1105A" (manufactured by Mitsui Chemicals, Inc.).
[0030] Commercially available examples of hydrocarbon waxes having a hydroxyl group and a carboxyl group include "PARACOL 6420", "PARACOL 6470", and "PARACOL 6490" (all manufactured by Nippon Seiro Co., Ltd.).
[0031] From the viewpoint of improving hiding power, the hydroxyl value of the hydrocarbon wax WA is preferably 35 mgKOH / g or more and preferably 180 mgKOH / g or less.
[0032] From the viewpoint of improving hiding power, the acid value of the hydrocarbon wax WA is preferably 1 mgKOH / g or more and preferably 30 mgKOH / g or less.
[0033] The total of the hydroxyl value and the acid value of the hydrocarbon wax WA is preferably 35 mgKOH / g or more and preferably 210 mgKOH / g or less, from the viewpoint of improving hiding power.
[0034] The number average molecular weight of the hydrocarbon wax WA is preferably 500 or more and preferably 2000 or less, from the viewpoint of improving hiding power. The hydroxyl value and acid value of the hydrocarbon wax WA are measured by the method described in the Examples. The number average molecular weight of the hydrocarbon wax WA is measured by gel permeation chromatography using chloroform as a solvent and polystyrene as a standard substance.
[0035] The content of the polyester resin segment in the composite resin A is preferably 40% by mass or more, more preferably 45% by mass or more, even more preferably 50% by mass or more, and preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 75% by mass or less, even more preferably 70% by mass or less, based on the total amount of the polyester resin segment and the addition polymerization resin segment. Note that the constitutional unit derived from the bireactive monomer is included in the calculation of the polyester resin segment.
[0036] The content of the addition polymerization resin segment in the composite resin A is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 25% by mass or more, and is preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 45% by mass or less, based on the total amount of the polyester resin segment and the addition polymerization resin segment. Note that the constitutional unit derived from the bireactive monomer is calculated by including it in the polyester resin segment.
[0037] The amount of the constitutional units derived from the bireactive monomer in the composite resin A is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 0.8 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, based on the total amount of the polyester resin segment and the addition polymerization resin segment.
[0038] The amount of the constituent units derived from the hydrocarbon wax WA in the composite resin A is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1 part by mass or more, even more preferably 3 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, even more preferably 6 parts by mass or less, relative to 100 parts by mass of the total amount of the polyester resin segment and the addition polymerization resin segment. The constituent units derived from the bireactive monomer are calculated by including them in the polyester resin segment.
[0039] In the composite resin A, the total amount of the polyester resin segment, the addition polymerization resin segment, the constitutional units derived from the bireactive monomer, and the constitutional units derived from the hydrocarbon wax WA is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and is 100 mass% or less, more preferably 100 mass%.
[0040] The above amount is calculated based on the ratio of the amounts of the polyester resin segment, raw material monomer for the addition polymerization resin segment, bireactive monomer, structural unit derived from the hydrocarbon wax WA, and radical polymerization initiator, and does not include the amount of dehydration due to polycondensation in the polyester resin segment, etc. When a radical polymerization initiator is used, the mass of the radical polymerization initiator is included in the calculation of the addition polymerization resin segment.
[0041] The composite resin A may be produced, for example, by a method including a step A of carrying out a polycondensation reaction between an alcohol component and a carboxylic acid component, and a step B of carrying out an addition polymerization reaction between a raw material monomer for the addition polymerization resin segment and a bireactive monomer. When the composite resin A has a structural unit derived from a hydrocarbon wax WA, in the above-mentioned step A, for example, a polycondensation reaction of an alcohol component and a carboxylic acid component is carried out in the presence of a hydrocarbon wax WA having at least one of a hydroxyl group and a carboxyl group. Step B may be carried out after step A, step B may be carried out after step A, or step A and step B may be carried out simultaneously. In the step A, a part of the carboxylic acid component is subjected to a polycondensation reaction, and then the step B is carried out, and thereafter the remainder of the carboxylic acid component is added to the polymerization system, and the polycondensation reaction of the step A and the reaction with the bireactive monomer, if necessary, are further promoted.
[0042] In step A, if necessary, polycondensation may be performed using an esterification catalyst such as tin(II) di(2-ethylhexanoate), dibutyltin oxide, titanium diisopropylate bistriethanolamine, etc., in an amount of 0.01 part by mass or more and 5 parts by mass or less per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component; or an esterification promoter such as gallic acid (same as 3,4,5-trihydroxybenzoic acid), etc., in an amount of 0.001 part by mass or more and 0.5 part by mass or less per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. In addition, when a monomer having an unsaturated bond such as fumaric acid is used in the polycondensation reaction, a radical polymerization inhibitor may be used, if necessary, in an amount of preferably 0.001 to 0.5 parts by mass per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. An example of the radical polymerization inhibitor is 4-tert-butylcatechol. The temperature of the polycondensation reaction is preferably 120° C. or higher, more preferably 160° C. or higher, and even more preferably 180° C. or higher, and is preferably 250° C. or lower, more preferably 240° C. or lower. The polycondensation may be carried out in an inert gas atmosphere.
[0043] Examples of the polymerization initiator for the addition polymerization reaction include peroxides such as dibutyl peroxide, persulfates such as sodium persulfate, and azo compounds such as 2,2'-azobis(2,4-dimethylvaleronitrile). The amount of the radical polymerization initiator used is preferably 1 part by mass or more and 20 parts by mass or less based on 100 parts by mass of the raw material monomer of the addition polymerization resin segment. The temperature of the addition polymerization reaction is preferably 110° C. or higher, more preferably 130° C. or higher, and preferably 220° C. or lower, more preferably 200° C. or lower, and further preferably 180° C. or lower.
[0044] (Physical properties of composite resin A) The softening point of the composite resin A is preferably 70° C. or higher, more preferably 80° C. or higher, and even more preferably 90° C. or higher, and is preferably 140° C. or lower, and more preferably 130° C. or lower. The glass transition temperature of the composite resin A is preferably 30° C. or higher, more preferably 40° C. or higher, and preferably 80° C. or lower, more preferably 70° C. or lower, and even more preferably 60° C. or lower.
[0045] The acid value of the composite resin A is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 35 mgKOH / g or less. The softening point, glass transition temperature, and acid value of the composite resin A can be appropriately adjusted by adjusting the type and amount of the raw material monomer used, as well as the production conditions such as the reaction temperature, reaction time, and cooling rate, and these values can be determined by the methods described in the examples. When two or more types of composite resin A are used in combination, the softening point, glass transition temperature and acid value of the mixture are preferably within the above-mentioned ranges.
[0046] <Amorphous polyester resin B> In the present invention, the toner particles preferably contain, in addition to the above-mentioned amorphous composite resin A, an amorphous polyester resin B as a binder resin. The amorphous polyester resin B is preferably, for example, an amorphous polyester resin containing a polycondensate of an alcohol component and a carboxylic acid component.
[0047] The alcohol component may be an alkylene oxide adduct of an aromatic diol, a linear or branched aliphatic diol, an alicyclic diol, or a trivalent or higher polyhydric alcohol, similar to the alcohol component of the polyester resin segment of the amorphous composite resin A described above. Among these, from the viewpoint of obtaining a toner having excellent concealing properties, an alkylene oxide adduct of an aromatic diol is preferred, an alkylene oxide adduct of bisphenol A is more preferred, and a propylene oxide adduct of bisphenol A [2,2-bis(4-hydroxyphenyl)propane] and an ethylene oxide adduct of bisphenol A are even more preferred. These may be used alone or in combination. Among these, an ethylene oxide adduct of bisphenol A is more preferred.
[0048] Examples of the carboxylic acid component include the same dicarboxylic acids and trivalent or higher polyvalent carboxylic acids as the carboxylic acid component of the polyester resin segment of the amorphous composite resin A described above. Examples of dicarboxylic acids include aromatic dicarboxylic acids, linear or branched aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids. Among these, at least one selected from aromatic dicarboxylic acids and linear or branched aliphatic dicarboxylic acids is preferred. The amount of aromatic dicarboxylic acid in the carboxylic acid component is preferably 40 mol% or more, more preferably 50 mol% or more, even more preferably 60 mol% or more, even more preferably 70 mol% or more, even more preferably 80 mol% or more, and is preferably 95 mol% or less, more preferably 90 mol% or less.
[0049] As the linear or branched aliphatic dicarboxylic acid, dodecenylsuccinic acid is preferred, and the amount thereof in the carboxylic acid component is preferably 1 mol % or more, more preferably 3 mol % or more, and preferably 60 mol % or less, more preferably 30 mol % or less, even more preferably 20 mol % or less, and even more preferably 10 mol % or less.
[0050] When a trivalent or higher polycarboxylic acid is contained, the amount of the trivalent or higher polycarboxylic acid in the carboxylic acid component is preferably 3 mol % or more, more preferably 5 mol % or more, and preferably 30 mol % or less, more preferably 20 mol % or less, and even more preferably 15 mol % or less. These carboxylic acid components may be used alone or in combination of two or more.
[0051] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0052] The polyester resin B may be produced, for example, by the step A of polycondensing an alcohol component and a carboxylic acid component. Step A is the same as step A described in the method for producing the amorphous composite resin A, and the preferred ranges are also the same.
[0053] (Physical properties of amorphous polyester resin B) The softening point of the amorphous polyester resin B is preferably 70° C. or higher, more preferably 90° C. or higher, and even more preferably 100° C. or higher from the viewpoint of the storage stability of the toner, and is preferably 150° C. or lower, more preferably 140° C. or lower, and even more preferably 125° C. or lower from the viewpoint of further improving the low-temperature fixing ability. The glass transition temperature of the amorphous polyester resin B is preferably 30° C. or higher, more preferably 40° C. or higher, even more preferably 50° C. or higher, and even more preferably 60° C. or higher, from the viewpoint of improving the low-temperature fixing ability, and is preferably 90° C. or lower, more preferably 80° C. or lower, and even more preferably 70° C. or lower.
[0054] The acid value of the amorphous polyester resin B is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, even more preferably 15 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less, even more preferably 25 mgKOH / g or less. The softening point, glass transition temperature, and acid value of the amorphous polyester resin B can be appropriately adjusted by the types and amounts of raw material monomers used, as well as production conditions such as reaction temperature, reaction time, and cooling rate, and these values can be determined by the methods described in the examples. When two or more kinds of amorphous polyester resins B are used in combination, the softening point, glass transition temperature and acid value of the mixture thereof preferably fall within the above-mentioned ranges.
[0055] When amorphous polyester resin B is used, the mass ratio of amorphous composite resin A to amorphous polyester resin B (amorphous composite resin A / amorphous polyester resin B) is, from the viewpoint of hiding property, preferably 50 / 50 or more, more preferably 60 / 40 or more, even more preferably 70 / 30 or more, even more preferably 80 / 20 or more, and is preferably 95 / 5 or less, more preferably 90 / 10 or less.
[0056] <Crystalline polyester resin C> In the present invention, the binder resin preferably contains a crystalline polyester resin C in addition to the above-mentioned amorphous composite resin A and amorphous polyester resin B, from the viewpoint of obtaining a toner having excellent low-temperature fixing properties. The crystalline polyester resin C is, for example, a crystalline polyester resin which is a polycondensation product of an alcohol component and a carboxylic acid component. The alcohol component is preferably an α,ω-aliphatic diol. The α,ω-aliphatic diol has preferably 2 or more, more preferably 4 or more, even more preferably 6 or more, and preferably 16 or less, more preferably 14 or less, even more preferably 12 or less. Examples of α,ω-aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol. Among these, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred, and 1,10-decanediol is more preferred.
[0057] The amount of the α,ω-aliphatic diol in the alcohol component is preferably 80 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and is 100 mol % or less, even more preferably 100 mol %.
[0058] The alcohol component may contain other alcohol components different from the α,ω-aliphatic diol. Examples of the other alcohol components include aliphatic diols other than α,ω-aliphatic diols, such as 1,2-propanediol and neopentyl glycol; aromatic diols, such as alkylene oxide adducts of bisphenol A; and trihydric or higher alcohols, such as glycerin, pentaerythritol, and trimethylolpropane. These alcohol components may be used alone or in combination.
[0059] The carboxylic acid component is preferably an aliphatic dicarboxylic acid, more preferably a straight-chain aliphatic dicarboxylic acid. The aliphatic dicarboxylic acid has preferably 4 or more, more preferably 8 or more, and even more preferably 10 or more carbon atoms, and preferably 14 or less, and more preferably 12 or less. Examples of the aliphatic dicarboxylic acid include fumaric acid, sebacic acid, dodecanedioic acid, and tetradecanedioic acid. Among these, sebacic acid and tetradecanedioic acid are preferred, and sebacic acid is more preferred. These carboxylic acid components may be used alone or in combination.
[0060] The amount of the aliphatic dicarboxylic acid in the carboxylic acid component is preferably 80 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and is 100 mol % or less, even more preferably 100 mol %.
[0061] The carboxylic acid component may contain other carboxylic acid components different from the aliphatic dicarboxylic acid. Examples of other carboxylic acid components include aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid, and polyvalent carboxylic acids having three or more carboxylic acids. These carboxylic acid components may be used alone or in combination.
[0062] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0063] The crystalline polyester resin C is produced, for example, by a method of polycondensing an alcohol component and a carboxylic acid component. During polycondensation, if necessary, an esterification catalyst such as tin(II) di(2-ethylhexanoate), dibutyltin oxide, or titanium diisopropoxybis(triethanolaminate) may be used in an amount of 0.01 part by mass or more and 5 parts by mass or less per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component; or an esterification promoter such as gallic acid (same as 3,4,5-trihydroxybenzoic acid) may be used in an amount of 0.001 part by mass or more and 0.5 part by mass or less per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. When a monomer having an unsaturated bond such as fumaric acid is used in polycondensation, a radical polymerization inhibitor may be used, if necessary, in an amount of preferably 0.001 to 0.5 parts by mass per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. An example of the radical polymerization inhibitor is 4-tert-butylcatechol. The temperature of the polycondensation reaction is preferably 120° C. or higher, more preferably 160° C. or higher, and even more preferably 180° C. or higher, and is preferably 250° C. or lower, more preferably 240° C. or lower. The polycondensation may be carried out in an inert gas atmosphere.
[0064] (Physical properties of crystalline polyester resin C) The softening point of the crystalline polyester resin C is preferably 60°C or higher, more preferably 70°C or higher, and even more preferably 80°C or higher from the viewpoint of the storage stability of the toner, and is preferably 150°C or lower, more preferably 120°C or lower, and even more preferably 100°C or lower from the viewpoint of further improving the low-temperature fixing ability. The melting point of the crystalline polyester resin C is preferably 50°C or higher, more preferably 60°C or higher, and even more preferably 70°C or higher from the viewpoint of the storage stability of the toner, and is preferably 100°C or lower, more preferably 90°C or lower, and even more preferably 85°C or lower from the viewpoint of further improving the low-temperature fixing ability.
[0065] The acid value of the crystalline polyester resin C is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, and is preferably 35 mgKOH / g or less, more preferably 25 mgKOH / g or less.
[0066] The softening point, melting point and acid value of the crystalline polyester resin C can be appropriately adjusted by the type and amount of the raw material monomer, as well as production conditions such as reaction temperature, reaction time and cooling rate, and are determined by the method described in the Examples below. When two or more types of crystalline polyester resin C are used in combination, it is preferable that the softening point, melting point and acid value obtained as a mixture thereof are each within the above-mentioned ranges.
[0067] When crystalline polyester C is used as the binder resin, the mass ratio of amorphous polyester resin A to crystalline polyester resin C [amorphous polyester resin A / crystalline polyester resin C] is preferably 40 / 60 or more, more preferably 60 / 40 or more, even more preferably 65 / 35 or more, and is preferably 95 / 5 or less, more preferably 90 / 10 or less, even more preferably 85 / 15 or less.
[0068] [Coloring Agent] In the colorant (hereinafter also referred to as "colorant Z"), from the viewpoint of obtaining a toner having excellent hiding power, titanium oxide is coated with an addition polymer (hereinafter also referred to as "addition polymer E") of raw material monomers including an addition polymerizable monomer having an anionic group and an addition polymerizable monomer having a polyalkylene oxide group. Note that "titanium oxide is coated with an addition polymer" refers to a state in which an addition polymer is adsorbed to titanium oxide. Although it is sufficient that at least a part of the surface of titanium oxide is coated with the addition polymer E, it is preferable that the entire titanium oxide is coated with the addition polymer E. Whether titanium oxide is coated with the addition polymer E can be identified by analyzing a cut surface of the colorant. Specifically, it can be identified by analyzing a resin in contact with titanium oxide on the cut surface.
[0069] (Titanium dioxide) The colorant contains titanium oxide, which is a white pigment. As the titanium oxide, rutile type titanium oxide or anatase type titanium oxide can be used, but from the viewpoints of stability and availability, rutile type titanium oxide is preferred. From the viewpoint of obtaining good dispersibility in the toner, titanium oxide is preferably surface-treated. The surface treatment of titanium oxide is not particularly limited, and may be either surface treatment with an organic substance or surface treatment with an inorganic substance. From the viewpoint of avoiding the influence of photocatalysis, titanium oxide surface-treated with an inorganic substance is preferable, titanium oxide surface-treated with at least one of silica and alumina is more preferable, and titanium oxide surface-treated with silica and alumina is even more preferable. By calcining the surface-treated titanium oxide powder at a temperature of 800° C. or higher and 1000° C. or lower, sintering between particles can be suppressed, and the fluidity and dispersibility of the titanium oxide can be improved. The particle shape of the titanium oxide is exemplified by granular and needle-like shapes, but is not particularly limited.
[0070] The average primary particle size of titanium oxide is, from the viewpoint of obtaining a desired particle size of the colorant and from the viewpoint of obtaining a high whiteness, preferably 100 nm or more, more preferably 150 nm or more, even more preferably 200 nm or more, even more preferably 220 nm or more, even more preferably 230 nm or more, even more preferably 240 nm or more, and even more preferably 250 nm or more, and from the viewpoint of dispersibility, preferably 500 nm or less, more preferably 400 nm or less, even more preferably 390 nm or less, even more preferably 380 nm or less, even more preferably 340 nm or less, even more preferably 330 nm or less, even more preferably 320 nm or less, and even more preferably 300 nm or less. The average primary particle size of titanium oxide can be measured using a transmission electron microscope, specifically, 500 titanium oxide primary particles are extracted using image analysis using a transmission electron microscope, their particle sizes are measured, and the average is calculated to give the number average particle size. In addition, when titanium oxide has a major axis and a minor axis, the major axis is used for the calculation. Commercially available examples of titanium oxide for use in the present invention include trade names JR, JR-300, JR-605, and JR-701 manufactured by Teika Corporation, and trade names Typeque CR-93, CR-90, and CR-80 manufactured by Ishihara Sangyo Kaisha, Ltd.
[0071] (Addition polymer E) Addition polymer E is an addition polymer of raw material monomers including an addition polymerizable monomer having an anionic group (hereinafter also referred to as an "anionic group-containing monomer") and an addition polymerizable monomer having a polyalkylene oxide group, from the viewpoint of obtaining a toner having excellent dispersibility of titanium oxide and excellent hiding power, and from the viewpoint of low-temperature fixing property and chargeability.
[0072] <Addition-polymerizable monomer having an anionic group> The addition polymer E has a constitutional unit derived from an addition polymerizable monomer having an anionic group (anionic group-containing monomer), whereby an anionic group is introduced.
[0073] From the viewpoints of improving hiding power, low-temperature fixability and chargeability, the anionic group-containing monomer preferably has an anionic group selected from the group consisting of a carboxy group, a sulfonic acid group and a phosphoric acid group. Examples of addition polymerizable monomers having a carboxy group (carboxy group-containing monomers) include acrylic acid, methacrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, citraconic acid, and 2-methacryloyloxyethylsuccinic acid. Examples of addition polymerizable monomers having a sulfonic acid group (sulfonic acid group-containing monomers) include styrenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, 3-sulfopropyl(meth)acrylate, and bis-(3-sulfopropyl)itaconic acid. Examples of addition polymerizable monomers having a phosphoric acid group (phosphate group-containing monomers) include vinylphosphonic acid, vinyl phosphate, bis(methacryloxyethyl)phosphate, diphenyl-2-acryloyloxyethyl phosphate, diphenyl-2-methacryloyloxyethyl phosphate, and dibutyl-2-acryloyloxyethyl phosphate.
[0074] As the anionic group-containing monomer, from the viewpoint of improving the dispersibility of the colorant in the dispersion liquid and in the toner, a carboxy group-containing monomer is preferably used, more preferably at least one selected from acrylic acid and methacrylic acid, and even more preferably methacrylic acid. The anionic group-containing monomer may form a salt, and examples of the salt include sodium salt and potassium salt.
[0075] The content of the anionic group-containing monomer in the raw material monomers of the addition polymer E is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, from the viewpoints of excellent dispersibility of titanium oxide and improved hiding power, and low-temperature fixability and electrostatic chargeability, and is preferably 50% by mass or less, more preferably 35% by mass or less, even more preferably 20% by mass or less.
[0076] <Addition-polymerizable monomer having a polyalkylene oxide group> The raw material monomers for the addition polymer E used in the present invention contain, in addition to an anionic group-containing monomer, an addition polymerizable monomer having a polyalkylene oxide group (hereinafter, referred to as a polyalkylene oxide group-containing monomer). The polyalkylene oxide group-containing monomer is preferably a polyalkylene glycol (meth)acrylate, and the polyalkylene glycol (meth)acrylate is represented by the following formula (1).
[0077] [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 20 carbon atoms, OA represents an oxyalkylene group having 2 to 4 carbon atoms, and n represents the average number of moles of alkylene oxide added, which is a number of 4 to 300.
[0078] R 1 represents a hydrogen atom or a methyl group, and from the viewpoint of improving the hiding power, and from the viewpoint of low-temperature fixability and chargeability, a methyl group is preferable. R 2 represents a hydrogen atom or a monovalent hydrocarbon group having from 1 to 20 carbon atoms, and is preferably a monovalent hydrocarbon group having from 1 to 20 carbon atoms. Examples of the hydrocarbon group include an alkyl group and an aryl group, and an alkyl group is preferable. The alkyl group preferably has 1 to 8 carbon atoms, more preferably has 1 to 3 carbon atoms, and further preferably is a methyl group. The aryl group is preferably one having 6 to 10 carbon atoms, more preferably a phenyl group or a naphthyl group, and even more preferably a phenyl group. OA represents an oxyalkylene group having from 2 to 4 carbon atoms, preferably an oxyethylene group or an oxypropylene group, more preferably an oxyethylene group. The average number of moles of oxyalkylene groups added, n, is 4 or more, preferably 8 or more, more preferably 12 or more, even more preferably 18 or more, and is preferably 300 or less, more preferably 150 or less, even more preferably 100 or less, even more preferably 30 or less.
[0079] The content of the polyalkylene oxide group-containing monomer in the raw material monomers of the addition polymer E is preferably 50% by mass or more, more preferably 65% by mass or more, even more preferably 80% by mass or more, from the viewpoint of improving hiding power and low-temperature fixability and electrostatic property, and is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less.
[0080] The mass ratio of the anionic group-containing monomer to the polyalkylene oxide group-containing monomer (anionic group-containing monomer / alkylene oxide group-containing monomer) in the raw material monomers of the addition polymer E is, from the viewpoint of improving hiding power and from the viewpoints of low-temperature fixability and electrostatic chargeability, preferably 5 / 95 or more, more preferably 10 / 90 or more, even more preferably 15 / 85 or more, and is preferably 50 / 50 or less, more preferably 35 / 65 or less, even more preferably 20 / 80 or less.
[0081] <Hydrophobic monomer> In the present invention, the raw material monomers for the addition polymer may further contain a hydrophobic monomer in addition to the anionic group-containing monomer and the polyalkylene oxide group-containing monomer, as long as the effects of the present invention are not impaired. From the viewpoint of ease of production of the addition polymer E, examples of the hydrophobic monomer include alkyl (meth)acrylates and aromatic group-containing monomers. The alkyl (meth)acrylate is preferably a compound having an alkyl group having 1 to 22 carbon atoms, more preferably 6 to 18 carbon atoms, such as ethyl (meth)acrylate, (iso)propyl (meth)acrylate, (iso- or tertiary)butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Examples of aromatic group-containing monomers include styrene, α-methylstyrene, benzyl (meth)acrylate, and phenoxy (meth)acrylate. When the raw material monomer contains a hydrophobic monomer, the content of the hydrophobic monomer in the raw material monomer is preferably 0.1% by mass or more and preferably 5% by mass or less.
[0082] From the viewpoints of excellent dispersibility of titanium oxide and further improving hiding power, as well as low-temperature fixability and electrostatic chargeability, the weight-average molecular weight of the addition polymer E is preferably 3,000 or more, more preferably 20,000 or more, even more preferably 40,000 or more, even more preferably 48,000 or more, and is preferably 200,000 or less, more preferably 80,000 or less, even more preferably 70,000 or less. The weight-average molecular weight can be measured by the method described in the Examples.
[0083] From the viewpoints of excellent dispersibility of titanium oxide and further improving hiding power, as well as low-temperature fixability and electrostatic chargeability, the acid value of the addition polymer E is preferably 30 mgKOH / g or more, more preferably 80 mgKOH / g or more, and even more preferably 100 mgKOH / g or more, and is preferably 500 mgKOH / g or less, more preferably 300 mgKOH / g or less, and even more preferably 150 mgKOH / g or less. The acid value of the addition polymer E is measured by the method described in the Examples.
[0084] The addition polymer E can be produced, for example, by copolymerizing raw material monomers by a known polymerization method such as a solution polymerization method, a suspension polymerization method, an emulsion polymerization method, etc. Among these, the polymerization method is preferably a solution polymerization method in which raw material monomers are polymerized by heating in a solvent together with a polymerization initiator, a polymerization chain transfer agent, etc. The solvent used in the solution polymerization method is not particularly limited, but from the viewpoint of facilitating the preparation of the colorant dispersion liquid, it is preferable to use an aqueous medium. The aqueous medium means a medium mainly composed of water. In addition to water, an organic solvent may be added, and examples of the organic solvent other than water include aliphatic alcohols having 1 to 4 carbon atoms, ketones having 3 to 8 carbon atoms, ethers such as ethyl ether, propyl ether, and tetrahydrofuran, and esters such as methyl acetate and ethyl acetate. The content of water in the aqueous medium is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably 100% by mass.
[0085] Examples of the polymerization initiator include peroxides such as dibutyl peroxide, persulfates such as ammonium persulfate and sodium persulfate, and azo compounds such as 2,2'-azobis(2,4-dimethylvaleronitrile). The amount of the polymerization initiator added is preferably 0.5 parts by mass or more and preferably 30 parts by mass or less based on 100 parts by mass of the raw material monomer. Examples of the polymerization chain transfer agent include mercaptans such as 2-mercaptoethanol and 3-mercaptopropionic acid. The amount of the polymerization chain transfer agent added is preferably 0.01 parts by mass or more and preferably 10 parts by mass or less based on 100 parts by mass of the raw material monomer. Preferred polymerization conditions vary depending on the type of polymerization initiator, raw material monomer, solvent, etc. used, but the polymerization temperature is preferably 30° C. or higher, more preferably 60° C. or higher, and preferably 95° C. or lower, more preferably 85° C. or lower. The polymerization time is preferably 1 hour or longer, more preferably 2 hours or longer, and preferably 20 hours or shorter, more preferably 10 hours or shorter. The polymerization atmosphere is preferably a nitrogen gas atmosphere, an inert gas atmosphere such as argon, etc.
[0086] In the colorant, the mass ratio of titanium oxide to addition polymer E (titanium oxide / addition polymer E) is, from the viewpoints of excellent dispersibility of titanium oxide and further improving hiding power, as well as low-temperature fixability and electrostatic property, preferably 50 / 50 or more, more preferably 70 / 30 or more, even more preferably 85 / 15 or more, even more preferably 90 / 10 or more, even more preferably 95 / 5 or more, and is preferably 99.5 / 0.5 or less, more preferably 99.2 / 0.8 or less.
[0087] [Method for producing colorant Z] The colorant Z can be obtained by mixing titanium oxide and an addition polymer E, for example. There is no particular limitation on the method for producing the dispersion of colorant Z, and any method can be used as long as a colorant having a desired particle size can be obtained using a known kneader, disperser, or the like. Preferably, the dispersion is obtained by mixing titanium oxide and a dispersion of addition polymer E using a bead mill or homogenizer.
[0088] The method for producing the dispersion of colorant Z is preferably Step a: obtaining an aqueous dispersion of a neutralized addition polymer E; and Step b: A step of dispersing the dispersion obtained in step a with titanium oxide to obtain a dispersion of colorant Z. It is a method having the following structure. Moreover, the step b is preferably a step of dispersing the dispersion liquid obtained in the step a and titanium oxide with a bead mill or a homogenizer.
[0089] The neutralizing agent may, for example, be a basic substance, such as an alkali metal hydroxide, such as sodium hydroxide, potassium hydroxide, or a nitrogen-containing basic substance, such as ammonia, trimethylamine, or diethanolamine. The degree of neutralization of the addition polymer E is preferably 10 mol% or more, more preferably 20 mol% or more, even more preferably 30 mol% or more, and preferably 100 mol% or less, more preferably 80 mol% or less, even more preferably 60 mol% or less, even more preferably 50 mol% or less. The degree of neutralization of the addition polymer E can be calculated by the following formula. Degree of neutralization (mol%)=[{weight (g) of neutralizing agent added / equivalent weight of neutralizing agent} / {weight ratio of addition polymerizable monomer having an acidic group constituting addition polymer E×weight (g) of addition polymer E / molecular weight of addition polymerizable monomer having an acidic group}]×100 When the calculated degree of neutralization exceeds 100, the degree of neutralization is taken to be 100 mol %.
[0090] In the step b, the mass ratio of titanium oxide to addition polymer E [titanium oxide / addition polymer E] is as described above.
[0091] Examples of the apparatus used in step b include kneaders such as roll mills and kneaders, homogenizers such as Microfluidizer (manufactured by Microfluidic Corp.) and Starburst (manufactured by Sugino Machine Corp.), and media-type dispersers such as paint shakers and bead mills. Two or more of these apparatuses may be combined. Among these, from the viewpoint of reducing the particle size of titanium oxide, it is preferable to use a media-type disperser such as a bead mill or a homogenizer, and it is more preferable to use a media-type disperser. When using a media-type dispersing machine, the material of the media is preferably ceramics such as zirconia and titania, polymeric materials such as polyethylene and polyamide, metals, etc., and zirconia is preferable from the viewpoint of wear, etc. The shape of the media is not particularly limited, but is preferably bead-like (spherical). The dispersion time is preferably 0.3 hours or more, more preferably 1 hour or more, from the viewpoint of sufficiently finely pulverizing the colorant, and is preferably 100 hours or less, more preferably 50 hours or less, and even more preferably 20 hours or less, from the viewpoint of production efficiency of the colorant dispersion.
[0092] The dispersion of colorant Z is preferably filtered through a wire mesh or the like to remove coarse particles, etc. When titanium oxide is dispersed using a bead mill, removal of the bead mill and removal of the coarse particles may be carried out simultaneously. In addition, various additives such as organic solvents, preservatives, and antifungal agents may be added to the dispersion of colorant Z.
[0093] In the dispersion of colorant Z, the content of titanium oxide is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 20% by mass or more, even more preferably 25% by mass or more, and preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less. The solids concentration of the dispersion of colorant Z is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 20% by mass or more, and is preferably 70% by mass or less, more preferably 50% by mass or less, even more preferably 35% by mass or less.
[0094] Colorant Z may be used in the form of a dispersion, but the dispersion may be filtered to separate the solid content, which may then be washed as necessary and dried before use.
[0095] Volume median particle size D of colorant Z 50From the viewpoint of obtaining a toner having excellent hiding power, is preferably 0.10 μm or more, more preferably 0.15 μm or more, even more preferably 0.20 μm or more, even more preferably 0.23 μm or more, even more preferably 0.24 μm or more, even more preferably 0.25 μm or more, even more preferably 0.27 μm or more, and is preferably 0.55 μm or less, more preferably 0.45 μm or less, even more preferably 0.40 μm or less, even more preferably 0.35 μm or less, even more preferably 0.34 μm or less, even more preferably 0.33 μm or less, even more preferably 0.32 μm or less, and even more preferably 0.30 μm or less. Volume median particle size D of colorant Z 50 From the viewpoint of improving hiding power, the CV value is preferably 10% or more, more preferably 20% or more, even more preferably 25% or more, and is preferably 45% or less, more preferably 40% or less, even more preferably 35% or less. Volume median particle size D of colorant Z 50 and CV values are measured by the methods in the Examples.
[0096] From the viewpoint of further improving the hiding power and from the viewpoint of low-temperature fixability and chargeability, the content of titanium oxide in the toner particles is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, and is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 45% by mass or less.
[0097] [Release Agent] The toner particles may contain a release agent in addition to the above-mentioned binder resin and colorant. Examples of the release agent include hydrocarbon waxes such as polypropylene wax, polyethylene wax, polypropylene-polyethylene copolymer wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, or oxides thereof; ester waxes such as carnauba wax, montan wax, or deacidified waxes thereof, and fatty acid ester wax; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. These may be used alone or in combination of two or more. Among these, the hydrocarbon waxes and ester waxes are preferred, and the hydrocarbon waxes are more preferred.
[0098] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, and is preferably 160° C. or lower, more preferably 140° C. or lower, and further preferably 120° C. or lower.
[0099] The amount of the release agent in the toner is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 5% by mass or more, and preferably 30% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less, even more preferably 10% by mass or less.
[0100] The toner may contain other additives, such as a charge control agent, a magnetic powder, a flowability improver, a conductivity adjuster, a reinforcing filler such as a fibrous substance, an antioxidant, an antiaging agent, and a cleaning property improver.
[0101] <Method of manufacturing toner particles> The method for producing the toner particles is not particularly limited, and the toner particles may be produced by a chemical method such as an emulsion polymerization method or a suspension method, or may be produced by a kneading and pulverizing method. From the viewpoint of obtaining a toner having excellent low-temperature fixing properties, it is preferable to produce the toner particles by a chemical method such as an emulsion polymerization method or a suspension method. Furthermore, from the viewpoint of obtaining a toner having excellent toner physical properties such as low-temperature fixing properties, it is preferable to obtain the toner particles by an emulsion aggregation method having the following steps 1 to 3. Step 1: A step of aggregating resin particles X, which contain an amorphous composite resin A and a crystalline polyester resin C in the same or different particles, and a colorant Z in an aqueous medium to obtain aggregated particles 1; Step 2: A step of aggregating resin particles Y containing an amorphous polyester-based resin B to the aggregated particles 1 obtained in step 1 to obtain aggregated particles 2; Step 3: A step of heating the aggregated particles 2 obtained in step 2 to fuse them and obtain fused particles. As a method for producing toner particles by steps 1 to 3, for example, steps 1, 1', and 2 described in JP 2021-012242 A and steps 1, 1', and 2 described in JP 2021-026129 A can be referenced.
[0102] In the above step 1, it is preferable to aggregate the resin particles X and the colorant Z together with release agent particles containing a release agent. The dispersion of the resin particles X is preferably obtained by a phase inversion emulsification method. The release agent particles are preferably mixed with a resin particle dispersion and a colorant dispersion to prepare a dispersion of the release agent particles, and then aggregated, so that the release agent particles are contained in the aggregated particles. The dispersion of release agent particles can be obtained using a surfactant, but is preferably obtained by mixing the release agent with resin particles Z. By preparing the release agent particles using the release agent and resin particles S, the release agent particles are stabilized by the resin particles S, and it becomes possible to disperse the release agent in an aqueous medium without using a surfactant. It is considered that the dispersion of release agent particles has a structure in which a large number of resin particles S are attached to the surface of the release agent particles. The resin constituting the resin particles S in which the release agent is dispersed is preferably a polyester resin, and it is more preferable to use a composite resin D having a polyester resin segment and an addition polymerization resin segment. For the release agent particle dispersion and the composite resin D, reference is made to JP 2021-026129 A. In addition, a post-treatment step may be performed after the above step 3, and it is preferable to obtain toner particles by isolation. Since the particles obtained in step 3 are present in an aqueous medium, it is preferable to first perform solid-liquid separation, and then wash and dry them as necessary.
[0103] In the case of a pulverized toner by a kneading and pulverizing method, the method for producing the toner particles is preferably Step I: melting and kneading toner raw materials including a binder resin and a colorant; and Step II: A step of pulverizing and classifying the molten mixture obtained in step I to obtain toner particles. Includes. In step I, for example, toner raw materials such as a binder resin, a colorant, and a release agent can be uniformly mixed in a mixer such as a Henschel mixer, and then melt-kneaded in an internal kneader, a single-screw or twin-screw extruder, an open roll-type kneader, or the like. In step I, the mixture containing the above-mentioned toner raw materials may be melt-kneaded within a range of 80° C. or more and 160° C. or less. The melt-kneading temperature is preferably 80° C. or more, more preferably 90° C. or more, and is preferably 160° C. or less, more preferably 150° C. or less. In step I, the melt-kneaded product may be cooled after melt-kneading and then subjected to the next step II.
[0104] In the step II, the melt-kneaded product obtained by the melt-kneading is preferably pulverized and classified to obtain toner particles. The pulverization and classification can be performed by a known method. Furthermore, the obtained toner particles can be subjected to a spheronization step in which the toner shape is made spherical by a known method using a mechanical surface modifying device or a thermal surface modifying device.
[0105] [Volume average particle size of toner particles] The toner particles obtained by drying or the like may be used as they are as a white toner for developing electrostatic images. However, it is preferable to use the toner particles having an external additive, which will be described later, added to the surface of the toner particles as a white toner for developing electrostatic images. The volume median particle size of toner particles (D 50 ) is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, even more preferably 6 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 7 μm or less, from the viewpoints of improving toner productivity, obtaining a desired circularity, and improving the hiding power of the toner. The volume median particle size of toner particles (D 50From the viewpoint of improving the productivity of the toner, the CV value of is preferably 12% or more, more preferably 16% or more, and even more preferably 20% or more, and from the viewpoint of obtaining a high-quality image, it is preferably 35% or less, more preferably 30% or less, and even more preferably 28% or less. Volume median particle size of toner particles D 50 The CV value can be measured by the method described in the Examples.
[0106] [toner] The toner contains toner particles, which contain the above-mentioned binder resin and colorant, and further contain a release agent and the like, if necessary.
[0107] [External additives] The toner particles can be used as they are, but it is preferable to use the toner after adding a fluidizing agent or the like as an external additive to the surface of the toner particles. Examples of the external additive include fine particles of inorganic materials such as hydrophobic silica, titanium oxide, alumina, cerium oxide, and carbon black, and fine particles of polymers such as polycarbonate, polymethyl methacrylate, and silicone resin. Among these, hydrophobic silica is preferred. When the toner particles are surface-treated using an external additive, the amount of the external additive added is, relative to 100 parts by mass of the toner particles, preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 3 parts by mass or more, and preferably 5 parts by mass or less, more preferably 4.5 parts by mass or less, even more preferably 4 parts by mass or less.
[0108] Toners are used for developing electrostatic images in electrophotographic printing. The toners can be used, for example, as one-component developers or mixed with a carrier to form two-component developers. The white toner of the present invention is a white toner capable of forming an image with high concealment properties, and is therefore suitably used for the purpose of expressing white color and enhancing visibility in printing on recording media such as colored paper and resin film that are not white. The recording medium is not particularly limited, and examples thereof include plain paper ranging from thin paper to thick paper, high-quality paper, coated printing paper such as art paper and coated paper, commercially available Japanese paper, postcard paper, synthetic paper, resin film, cloth, and the like. Examples of the resin film include transparent synthetic resin films, such as polyester films, vinyl chloride films, polypropylene films, polyethylene films, nylon films, etc. Among these, polyester films and stretched polypropylene films are more preferred, and polyester films such as biaxially stretched polyethylene terephthalate (PET) films and polypropylene films such as biaxially stretched polypropylene (OPP) films are more preferred. The color of the recording medium is preferably a color that requires a white background (base layer) from the viewpoint of visibility, specifically a color other than colorless, transparent, and white. From the viewpoint of further improving the hiding property, the content of titanium oxide in the toner is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, and is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less. EXAMPLES
[0109] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Each property value was measured and evaluated by the following methods. In the notation "alkylene oxide (X)" and the like, the number X in parentheses means the average number of moles of alkylene oxide added.
[0110] [Measurement method] [Acid value and hydroxyl value of resin and hydrocarbon wax] Measurements were performed in accordance with JIS K0070:1992, except that the measurement solvent was chloroform.
[0111] [Resin softening point, maximum endothermic peak temperature, glass transition temperature] (1) Softening point Using a flow tester "CFT-500D" (Shimadzu Corporation), 1 g of sample was heated at a temperature increase rate of 6°C / min, while applying a load of 1.96 MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1 mm and a length of 1 mm. The plunger descent amount of the flow tester was plotted against the temperature, and the temperature at which half of the sample flowed out was taken as the softening point. (2) Crystallinity index Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of sample was weighed into an aluminum pan and cooled to 0°C at a rate of 10°C / min. The sample was then left to stand for 1 minute, after which it was heated to 180°C at a rate of 10°C / min and the calorific value was measured. The temperature of the peak with the largest peak area among the observed endothermic peaks was taken as the endothermic maximum peak temperature (1), and the crystallinity index was calculated by (softening point (°C)) / (endothermic maximum peak temperature (1) (°C)). (3) Melting point and glass transition temperature Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and cooled from that temperature to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min, and the calorific value was measured. Among the endothermic peaks observed, the temperature of the peak with the largest peak area was taken as the maximum endothermic peak temperature (2). In the case of a crystalline resin, this peak temperature was taken as the melting point. In the case of an amorphous resin, when a peak was observed, the temperature of the peak was taken as the glass transition temperature. When no peak was observed but a step was observed, the temperature at the intersection of the tangent showing the maximum slope of the curve at the step and an extension of the baseline on the low temperature side of the step was taken as the glass transition temperature.
[0112] [Measurement of weight average molecular weight of addition polymer E] Using a solution of 0.2 M phosphate buffer / acetonitrile = 9 / 1 (volume ratio) as an eluent, the measurement was performed by gel permeation chromatography (GPC apparatus (HLC-8320GPC) manufactured by Tosoh Corporation, columns (PW+G4000PW+G2500PW) manufactured by Tosoh Corporation, flow rate: 1.0 mL / min, temperature: 40°C) using polyethylene glycol, the weight average molecular weight of which had been previously determined to be monodisperse, as a standard substance.
[0113] [Measurement of acid value of addition polymer E] The measurement was performed according to the potentiometric titration method of JIS K 0070.
[0114] [Measurement of solids concentration in aqueous solution of addition polymer and colorant dispersion] 10.0 g of sodium sulfate, which had been kept constant in a desiccator, was weighed out into a 30 mL polypropylene container (φ=40 mm, height=30 mm), and about 1.0 g of the sample was added thereto and mixed, then accurately weighed, and maintained at 105°C for 2 hours to remove volatile matter, and further left in the desiccator for 15 minutes, and the mass was measured. The mass of the sample after removing the volatile matter was taken as the solid content, and divided by the mass of the sample added to obtain the solid content concentration (%).
[0115] [Melting point of release agent] Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and cooled to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min, the calorific value was measured, and the maximum endothermic peak temperature was taken as the melting point.
[0116] [Volume median particle size D of resin particles, release agent particles, and colorant 50 , CV value (1) Measuring device: Laser diffraction type particle size measuring device "LA-920" (manufactured by Horiba Ltd.) (2) Measurement conditions: Add distilled water to the measurement cell and measure the volume median particle size D at a concentration that brings the absorbance into the appropriate range. 50The volume average particle size was measured, and the CV value (coefficient of variation (particle size distribution)) was calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size) x 100
[0117] [Solid Content Concentration of Resin Particle Dispersion and Release Agent Particle Dispersion] Using an infrared moisture meter "FD-230" (Kett Electric Laboratory Co., Ltd.), the moisture content (mass%) of 5 g of the measurement sample was measured at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 min / fluctuation range 0.05%). The solid content concentration was calculated according to the following formula. Solid concentration (mass%) = 100-moisture (mass%)
[0118] [Average primary particle size of titanium oxide] The average primary particle size of titanium oxide was measured by embedding toner particles in acrylic resin, then using an ultramicrotome (ULTRACUT R, manufactured by LEICA) to prepare ultrathin slices of the toner cross-section with a length and width of approximately 100 μm × width of 100 μm and a thickness of 100 nm, and extracting 500 titanium oxide primary particles by image analysis using a transmission electron microscope "JEM-2100" (manufactured by JEOL Ltd.), measuring their particle sizes, and calculating the average of the particle sizes to obtain the number average particle size. When titanium oxide has a long diameter and a short diameter, the long diameter was used for the calculation. When 500 titanium oxide primary particles could not be extracted from one ultrathin sliced toner cross-section, image analysis was performed on multiple ultrathin sliced toner cross-sections.
[0119] [Volume median particle diameter of agglomerated particles D 50 and CV value] Volume median particle size of agglomerated particles D 50 was measured as follows: Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured and the volume median particle size D is calculated from the particle size distribution. 50 The volume average particle size was calculated. The CV value (coefficient of variation (particle size distribution)) was calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size) x 100
[0120] [Circularity of fused particles] The circularity of the fused particles was measured under the following conditions. Measurement equipment: Flow-type particle image analyzer "FPIA-3000" (Sysmex Corporation) Preparation of dispersion: A dispersion of fused particles was prepared by diluting with deionized water to a solids concentration of 0.001 to 0.05% by mass. Measurement mode: HPF measurement mode
[0121] [Volume median particle size of toner particles D 50 and CV value] Volume median particle size of toner particles D 50 was measured as follows: The measuring instrument, aperture diameter, analysis software, and electrolyte are the volume median particle diameter D 50 The same as above was used. Dispersion liquid: Polyoxyethylene lauryl ether "EMULGEN (registered trademark) 109P" (manufactured by Kao Corporation, HLB: 13.6) was dissolved in the electrolyte to obtain a dispersion liquid with a concentration of 5% by mass. Dispersion conditions: 10 mg of a toner measurement sample was added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser. Thereafter, 25 mL of electrolyte was added, and the mixture was further dispersed for 1 minute using an ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured and the volume median particle size D is calculated from the particle size distribution. 50 and the volume average particle size were determined. The CV value (%) was calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size) x 100
[0122] [Evaluation method] [Image density of printed matter (opacity) - 1] A colorless transparent PP label "KEP 70CA P2041 8KA" (manufactured by Lintec Corporation, thickness 70 μm) was printed with a commercially available printer "COREFIDO C712dnw" (manufactured by OKI Data Corporation) at a toner adhesion of 1.0 mg / cm 2 The solid image was output without being fixed. Next, the same printer was prepared with a modified temperature-variable fixing unit, the temperature of the fixing unit was set to 130° C., and the toner was fixed on an A4 sheet in portrait orientation at a speed of 1.7 seconds per sheet to obtain a printout. A colored wood-free paper "Super thick black made by Hokuetsu Kishu Paper Co., Ltd." was placed under the print, and the reflected image density of the solid image part of the output print was measured using a colorimeter "SpectroEye" (made by GretagMacbeth, light irradiation conditions: standard light source D50, observation field of view 2°, density standard DINNB, absolute white standard), and the values measured at any three points on the image were averaged to obtain the image density. The smaller the value, the better the hiding power.
[0123] [Image density of printed matter (opacity) - 2] The toner adhesion amount was 0.40 mg / cm on an untreated biaxially stretched PET film "FE2000" (manufactured by Futamura Chemical Co., Ltd., thickness 70 μm) using a commercially available printer "COREFIDO C712dnw" (manufactured by Oki Data Corporation). 2 The solid image was output without being fixed. Next, the same printer was prepared with a modified temperature-variable fixing unit, the temperature of the fixing unit was set to 150° C., and the toner was fixed on an A4 sheet in portrait orientation at a speed of 1.7 seconds per sheet to obtain a printout. A colored wood-free paper "Super thick black made by Hokuetsu Kishu Paper Co., Ltd." was placed under the print, and the reflected image density of the solid image part of the output print was measured using a colorimeter "SpectroEye" (made by GretagMacbeth, light irradiation conditions: standard light source D50, observation field of view 2°, density standard DINNB, absolute white standard), and the values measured at any three points on the image were averaged to obtain the image density. The smaller the value, the better the hiding power.
[0124] [Low Temperature Fixability of Toner] A colorless transparent PP label "KEP 70CA P2041 8KA" (manufactured by Lintec Corporation, thickness 70 μm) was printed with a commercially available printer "COREFIDO C712dnw" (manufactured by OKI Data Corporation) at a toner adhesion of 1.0 mg / cm 2 The solid image was output without being fixed. Next, the same printer was prepared with a modified temperature-variable fixing unit, the temperature of the fixing unit was set to 90° C., and the toner was fixed on an A4 sheet in portrait orientation at a speed of 1.7 seconds per sheet to obtain a printout. In the same manner, the temperature of the fixing unit was increased by 5° C. each time, and the toner was fixed to obtain a printed matter. A piece of mending tape, Scotch (registered trademark) Mending Tape 810 (manufactured by Sumitomo 3M Limited, width 18 mm), was cut to a length of 50 mm and lightly applied to the top margin of the printed image over the solid image, and then a 500 g cylindrical weight (contact area: 1963 mm 2 ) was placed on the print and pressed against it once at a speed of 10 mm / s. The applied tape was then peeled off from the bottom end at a peeling angle of 90° and a speed of 10 mm / s to obtain a print after the tape had been peeled off. 30 sheets of high-quality paper "Colored High-Quality Paper Blue Thick" (manufactured by Hokuetsu Corporation) were placed under the print before and after the tape had been applied, and the reflected image density of the fixed image portion of each print before and after the tape had been peeled off was measured using a colorimeter "SpectroEye" (manufactured by GretagMacbeth, light irradiation conditions: standard light source D50, observation field of view 2°, density standard DINNB, absolute white standard), and the fixing rate was calculated from each reflected image density according to the following formula. Fixation rate (%) = (reflection image density after tape peeling / reflection image density before tape application) x 100 The lowest temperature at which the fixing rate was 95% or more was determined as the minimum fixing temperature.
[0125] [Toner Charging Property] (Within one week of the obtained toner) 2.1 g of toner and 27.9 g of silicone ferrite carrier (manufactured by Kanto Denka Kogyo Co., Ltd., average particle size: 40 μm) were placed in a 50 mL cylindrical polypropylene bottle (manufactured by Nikko Hansen Co., Ltd.) at a temperature of 25°C and a relative humidity of 50%, and pre-mixed by shaking vertically and horizontally 10 times each. After that, they were mixed for 1 hour at a speed of 90 r / min using a Turbula mixer "T2F" (manufactured by Shinmaru Enterprises Co., Ltd.), and the charge amount was measured under the following conditions using a "q / m-meter" (manufactured by Epping Co., Ltd.). Mesh size: 635 mesh (opening: 24 μm, stainless steel) Soft blow: Blow pressure (1000V) ·Suction time: 90 seconds The charge amount is calculated by the following formula, and a larger absolute value indicates better chargeability. Charge amount (μC / g) = Total charge after 90 seconds (μC) / Amount of toner absorbed (g)
[0126] [Resin manufacturing] [Production of amorphous resin] Production Example A1 (Production of Resin A-1) The inside of a 10 L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 4,056 g of a propylene oxide (2.2) adduct of bisphenol A, 904 g of terephthalic acid, 30 g of tin(II) di(2-ethylhexanoate), 3.0 g of 3,4,5-trihydroxybenzoic acid (gallic acid), and 493 g of hydrocarbon wax "Parakol 6490" (manufactured by Nippon Seiro Co., Ltd., acid value 18 mg KOH / g, hydroxyl value 97 mg KOH / g) were placed in the flask. The mixture was heated to 235°C with stirring under a nitrogen atmosphere and maintained at 235°C for 8 hours, and then the pressure in the flask was reduced and maintained at 8 kPa for 1 hour. After that, the pressure was returned to atmospheric pressure, and then the mixture was cooled to 160°C. While the mixture was kept at 160°C, a mixture of 2,676g of styrene, 669g of stearyl methacrylate, 134g of acrylic acid, and 401g of dibutyl peroxide was added dropwise over 3 hours. After that, the mixture was kept at 160°C for 30 minutes, and then heated to 200°C. The pressure in the flask was further reduced and kept at 8kPa for 1 hour. After that, the mixture was returned to atmospheric pressure, and then cooled to 190°C. 215g of fumaric acid, 468g of sebacic acid, 223g of trimellitic anhydride, and 3.0g of 4-tert-butylcatechol were added, and the temperature was raised to 210°C at 10°C / hr. Then, the reaction was continued at 4kPa until the desired softening point, and resin A-1 was obtained. The physical properties are shown in Table 1.
[0127] Manufacturing Example B1 (Manufacturing of Resin B-1) The inside of a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 3,298 g of ethylene oxide (2.2) adduct of bisphenol A, 1,432 g of terephthalic acid, 25 g of tin (II) di(2-ethylhexanoate), and 2.5 g of 3,4,5-trihydroxybenzoic acid (gallic acid) were added, and the temperature was raised to 235°C while stirring under a nitrogen atmosphere, and after maintaining at 235°C for 6 hours, the pressure in the flask was further reduced and maintained at 8.3 kPa for 1 hour. After that, the pressure was returned to atmospheric pressure, and the flask was cooled to 180°C, and 130 g of dodecenylsuccinic anhydride and 140 g of trimellitic anhydride were added, and the temperature was raised to 220°C at 10°C / hr, and then the pressure in the flask was reduced and the reaction was carried out at 10 kPa until the desired softening point, and resin B-1 was obtained. The physical properties are shown in Table 1.
[0128] Manufacturing Example D1 (Manufacturing of Resin D-1) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 4,313g of a propylene oxide (2.2) adduct of bisphenol A, 818g of terephthalic acid, 727g of succinic acid, 30g of tin (II) di(2-ethylhexanoate), and 3.0g of 3,4,5-trihydroxybenzoic acid (gallic acid) were added, and the temperature was raised to 235°C while stirring under a nitrogen atmosphere, and the flask was kept at 235°C for 5 hours, after which the pressure in the flask was reduced and kept at 8kPa for 1 hour. After that, the pressure was returned to atmospheric pressure, and the flask was cooled to 160°C, and a mixture of 2,756g of styrene, 689g of stearyl methacrylate, 142g of acrylic acid, and 413g of dibutyl peroxide was added dropwise over 1 hour while the temperature was kept at 160°C. After that, the temperature was kept at 160° C. for 30 minutes, and then the temperature was raised to 200° C., and the pressure inside the flask was further reduced, and the reaction was carried out at 8 kPa until the desired softening point was reached, thereby obtaining Resin D-1. The physical properties are shown in Table 1.
[0129] [Table 1]
[0130] [Production of crystalline polyester resin] Manufacturing Example C1 (Manufacturing of Resin C-1) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, 3416g of 1,10-decanediol and 4084g of sebacic acid were added, and the temperature was raised to 135°C while stirring, and the mixture was kept at 135°C for 3 hours, and then the temperature was raised from 135°C to 200°C over 10 hours. Then, 23g of tin(II) di(2-ethylhexanoate) was added, and the mixture was kept at 200°C for another hour, after which the pressure in the flask was reduced and the mixture was kept under a reduced pressure of 8.3kPa for 1 hour to obtain resin C-1. The physical properties are shown in Table 2.
[0131] [Table 2]
[0132] [Production of resin particle dispersion] Production Example X1 (Production of Resin Particle Dispersion X-1) 210 g of Resin A-1, 90 g of Resin C-1, and 360 g of methyl ethyl ketone were placed in a 3 L vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and the resins were dissolved over 2 hours at 73° C. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization was 50 mol% relative to the acid value of the resin, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 600 g of deionized water was added over 60 minutes while stirring at 280 r / min (circumferential speed 88 m / min) to cause phase inversion emulsification. While continuing to maintain the temperature at 73°C, methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion. Thereafter, while continuing to stir at 280 r / min (circumferential speed 88 m / min), the aqueous dispersion was cooled to 30°C, and deionized water was added so that the solid concentration was 20 mass%, to obtain resin particle dispersion X-1. The volume median particle diameter D of the obtained resin particles was 50 and CV values are shown in Table 3.
[0133] Production Example Y1 (Production of Resin Particle Dispersion Y-1) 300 g of Resin B-1 and 300 g of methyl ethyl ketone were placed in a 3 L vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and the resin was dissolved over 2 hours at 40° C. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization with respect to the acid value of the resin was 60 mol%, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 40°C, 600g of deionized water was added over 60 minutes while stirring at 280r / min (circumferential speed 88m / min) to cause phase inversion emulsification. The temperature was raised to 73°C, and methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion. Thereafter, the aqueous dispersion was cooled to 30°C while stirring at 280r / min (circumferential speed 88m / min), and deionized water was added so that the solid concentration was 20 mass%, to obtain resin particle dispersion Y-1. The volume median particle diameter D of the obtained resin particles was 50 and CV values are shown in Table 3.
[0134] Production Example S1 (Production of Resin Particle Dispersion S-1) 200g of resin D-1 and 200g of methyl ethyl ketone were placed in a 3L container equipped with a stirrer, reflux condenser, dropping funnel, thermometer and nitrogen inlet tube, and the resin was dissolved at 73°C for 2 hours. A 5% by mass aqueous solution of sodium hydroxide was added to the obtained solution so that the degree of neutralization was 60mol% with respect to the acid value of resin D-1, and the solution was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 700g of deionized water was added over 50 minutes while stirring at 280r / min (circumferential speed 88m / min), and phase inversion emulsification was performed. While continuing to maintain the temperature at 73°C, methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion liquid. Thereafter, the aqueous dispersion liquid was cooled to 30°C while stirring at 280r / min (circumferential speed 88m / min), and deionized water was added so that the solid content concentration was 20% by mass, thereby obtaining a resin particle dispersion liquid S-1. The volume median particle diameter D of the obtained resin particles was 50 and CV values are shown in Table 3.
[0135] [Table 3]
[0136] [Production of release agent particle dispersion] Production Example W1 (Production of Release Agent Particle Dispersion W-1) Into a 1 L beaker were added 120 g of deionized water, 86 g of resin particle dispersion S-1, and 40 g of paraffin wax "HNP-9" (manufactured by Nippon Seiro Co., Ltd., melting point 75°C), and the mixture was melted by maintaining the temperature at 90 to 95°C and stirred to obtain a molten mixture. The obtained molten mixture was dispersed for 20 minutes using an ultrasonic homogenizer "US-600T" (manufactured by Nippon Seiki Seisakusho Co., Ltd.) while maintaining the temperature at 90 to 95°C, and then cooled to room temperature (20°C). Deionized water was added to adjust the solid content to 20% by mass, and a release agent particle dispersion W-1 was obtained. The volume median particle diameter D of the release agent particles in the dispersion was 50 The diameter was 0.47 μm and the CV value was 27%.
[0137] Production Example W2 (Production of Release Agent Particle Dispersion W-2) A release agent particle dispersion W-2 was obtained in the same manner as in Production Example W1, except that the type of release agent used was changed to Fischer-Tropsch wax "FNP-0090" (manufactured by Nippon Seiro Co., Ltd., melting point 90°C). 50 The diameter was 0.45 μm and the CV value was 28%.
[0138] [Production of Addition Polymer E] Manufacturing example E1 233g of water was charged into a 2L glass reaction vessel equipped with a dropping funnel, and the temperature was raised to 80°C under a nitrogen atmosphere. Next, under a nitrogen gas atmosphere, a monomer solution of 166g of methoxypolyethylene glycol monomethacrylate (average number of moles of ethylene oxide (EO) added n = 23, manufactured by Shin-Nakamura Chemical Co., Ltd., product name "NK Ester M-230G") and 34g of methacrylic acid as dropping solution 1, 27g of a 7% aqueous 2-mercaptoethanol solution as dropping solution 2, and 32g of a 6% aqueous ammonium persulfate solution as dropping solution 3 were each gradually dropped into the reaction vessel over 90 minutes at the same time. Next, 11g of an aqueous ammonium persulfate solution with a concentration of 6% was gradually dropped into the reaction vessel over 30 minutes, and after the completion of the dropping, the mixture was aged at 80°C for 1 hour. Thereafter, the mixture was cooled to 40° C., and neutralized by adding 13 g of a 48% aqueous sodium hydroxide solution (neutralization degree 40 mol%). Water was added so that the solid concentration became 40%, to obtain an aqueous solution of addition polymer E-1.
[0139] Manufacturing examples E2~E4 Aqueous solutions of addition polymers E-2 to E-4 were obtained in the same manner as in Production Example E1, except that the monomers and amounts thereof were changed as shown in Table 4. The details of the monomers in Table 4 are as follows. MPEGMA (n=23): Methoxypolyethyleneglycol methacrylate (average number of EO moles added = 23, manufactured by Shin-Nakamura Chemical Co., Ltd., product name "NK Ester M-230G") MPEGMA (n=9): Methoxypolyethyleneglycol methacrylate (average number of EO moles added = 9, manufactured by Shin-Nakamura Chemical Co., Ltd., product name "NK Ester M-90G") MPEGMA (n=120): methoxypolyethylene glycol methacrylate (average number of moles of EO added=120, used was that produced in Production Example I below.) Manufacturing example I (Production of methoxypolyethylene glycol methacrylate (n=120)) Using polyethylene glycol monomethyl ether (weight average molecular weight 5,300) having an average EO addition mole number of 120 melted at 80°C, the target product, methoxypolyethylene glycol methacrylate (average EO addition mole number = 120), was obtained by the method described in Example 1 of JP-A-11-228636.
[0140] [Table 4]
[0141] (Production of Colorant Dispersion) Manufacturing example Z1 In a 250 mL polyethylene bottle, 0.765 g (effective content 0.306 g) of the aqueous solution of the addition polymer E-1 obtained in Production Example E1 (solid content concentration 40%), 15 g of titanium oxide (CR-80 manufactured by Ishihara Sangyo Kaisha, Ltd., rutile type, Al, Si treatment, average primary particle size 250 nm), 15.3 g of water were added, and 369 g of zirconia beads (diameter 2 mm) were added, and dispersion was performed for 8 hours at 25° C. using a benchtop pot mill stand (manufactured by AS ONE Corporation). The zirconia beads were removed using a mesh, and the solid content concentration was adjusted with water to obtain colorant dispersion liquid Z-1 (solid content concentration 30 mass %).
[0142] Manufacturing examples Z2 and Z3 Except for changing the titanium oxide used as shown in Table 5, the same procedures as in Production Example Z1 were carried out to obtain colorant dispersions Z-2 and Z-3 (solid content 30% by mass). The titanium oxide used is as follows: Titanium oxide T2: CR-93 (manufactured by Ishihara Sangyo Kaisha, rutile type, alumina, silica treatment, average primary particle size 280 nm) Titanium oxide T3: JR-300 (manufactured by Teika Corporation, rutile type, alumina treatment, average primary particle size 320 nm)
[0143] Manufacturing example Z4~Z6 Colorant dispersions Z-4 to Z-6 (solid concentration 30% by mass) were obtained in the same manner as in Production Example Z2, except that the addition polymer E-1 in Production Example Z2 was changed to the addition polymer shown in Table 5.
[0144] Manufacturing examples Z7 and Z8 Colorant dispersions Z-7 and Z-8 (solid concentration 30% by mass) were obtained in the same manner as in Production Example Z2, except that the mass ratio of titanium oxide and the addition polymer in Production Example Z2 was changed to that shown in Table 5.
[0145] Manufacturing example Z9 In a 250 mL polyethylene bottle, 2.04 g (active content 0.31 g) of 15 mass% sodium dodecylbenzenesulfonate aqueous solution "Neopelex G-15" (Kao Corporation, anionic surfactant, LAS), 15 g of titanium oxide (Ishihara Sangyo Kaisha, Ltd. CR-93, rutile type, alumina, silica treatment, average particle size 280 nm), 15.3 g of water were added, and 369 g of zirconia beads were added, and dispersion was performed for 8 hours at 25 ° C. using a benchtop pot mill stand (AS ONE Corporation). The zirconia beads were removed using a mesh, and the solid content was adjusted with water to obtain colorant dispersion liquid Z-9 (solid content concentration 30 mass %).
[0146] Manufacturing example Z10 In a 250 mL polyethylene bottle, 0.31 g of polyoxyethylene distyrenated phenyl ether "EMULGEN A-60" (Kao Corporation, nonionic surfactant), 15 g of titanium oxide (Ishihara Sangyo Kaisha, Ltd. CR-93, rutile type, alumina, silica treatment, average particle size 280 nm), 15.3 g of water were added, and 369 g of zirconia beads were added, and dispersion was performed for 8 hours at 25 ° C. using a benchtop pot mill stand (AS ONE Corporation). The zirconia beads were removed using a mesh, and the solid concentration was adjusted with water to obtain colorant dispersion liquid Z-10 (solid concentration 30 mass %).
[0147] [Table 5]
[0148] [Toner manufacturing] Example 1 (Preparation of Toner 1) In a 3 L four-neck flask equipped with a dehydration tube, a stirrer and a thermocouple, 400 g of resin particle dispersion X-1, 36 g of release agent particle dispersion W-1, 36 g of release agent particle dispersion W-2, 177 g of colorant dispersion Z-1, 8 g of a 10 mass% aqueous solution of polyoxyethylene (50) lauryl ether "EMULGEN 150" (manufactured by Kao Corporation, nonionic surfactant), and 5 g of a 15 mass% aqueous solution of sodium dodecylbenzenesulfonate "NEOPELEX G-15" (manufactured by Kao Corporation, anionic surfactant) were mixed at a temperature of 25° C. Next, an aqueous solution obtained by dissolving 37 g of ammonium sulfate in 550 g of deionized water and adding 43 g of a 4.8 mass% aqueous solution of potassium hydroxide was added dropwise at 25° C. over 10 minutes while stirring the mixture, and then the temperature was raised to 55° C. over 2 hours to obtain the volume median particle diameter D of the aggregated particles. 50 The temperature was maintained at 55° C. until the particle diameter reached 6.7 μm, to obtain a dispersion of aggregated particles. The aggregated particle dispersion was cooled to 49° C., and while maintaining the temperature at 49° C., 48 g of resin particle dispersion Y-1 was added over 90 minutes to obtain an aggregated particle dispersion in which resin particles were aggregated to aggregated particles. To the obtained dispersion of aggregated particles, 226 g of sodium polyoxyethylene lauryl ether sulfate "EMAL E-27C" (Kao Corporation, anionic surfactant, effective concentration 27% by mass) and 1,584 g of deionized water were added. The temperature was then raised to 75°C over one hour, and the temperature was maintained at 75°C until the circularity reached 0.970, thereby obtaining a dispersion of fused particles in which the aggregated particles were fused together. The obtained dispersion of fused particles was cooled to 30° C., and the solid matter was separated by suction filtration, washed with deionized water at 25° C., and then vacuum dried at 30° C. for 48 hours to obtain toner particles. The physical properties of the obtained toner particles are shown in Table 6. 100 parts by mass of the toner particles, 2.5 parts by mass of hydrophobic silica "RY50" (manufactured by Nippon Aerosil Co., Ltd., number average particle size: 0.04 μm), and 1.0 part by mass of hydrophobic silica "Cabosil (registered trademark) TS720" (manufactured by Cabot Japan Co., Ltd., number average particle size: 0.012 μm) were placed in a Henschel mixer, stirred, and passed through a 150 mesh sieve to obtain toner 1. The obtained toner was evaluated, and the results are shown in Table 6.
[0149] Examples 2 to 7, Comparative Examples 1 to 3 (Production of toners 2-7, 9-11) A toner was prepared in the same manner as in Example 1, except that the types of resin particle dispersion liquid and colorant dispersion liquid used were changed as shown in Table 6. The physical properties of the obtained toner particles and the evaluation results of the toner are shown in Table 6. In Example 6, the amount of colorant dispersion used was changed to 175 g, and in Example 7, the amount of colorant dispersion used was changed to 191 g.
[0150] Example 8 (Preparation of Toner 8) The colorant dispersion Z-2 was subjected to suction filtration to separate the solid content, which was then washed with deionized water at 25° C. and vacuum dried at 30° C. for 48 hours to obtain titanium oxide particles. 38 parts by mass of binder resin A-1, 5 parts by mass of binder resin B-1, 16 parts by mass of binder resin C-1, and as a release agent, 4 parts by mass of paraffin wax "HNP-9" (manufactured by Nippon Seiro Co., Ltd., melting point 75°C) and 4 parts by mass of Fischer-Tropsch wax "FNP-0090" (manufactured by Nippon Seiro Co., Ltd., melting point 90°C), and 33 parts by mass of the obtained titanium oxide particles were mixed for 1 minute using a Henschel mixer and then melt-kneaded under the conditions shown below. Co-rotating twin screw extruder "PCM-30" (manufactured by Ikegai Corporation, shaft diameter 2.9 cm, shaft cross-sectional area 7.06 cm 2 The operating conditions were: barrel temperature 120°C, shaft rotation speed 200 r / min (shaft rotation peripheral speed 0.30 m / sec), mixture supply speed 10 kg / h (mixture supply amount per unit cross-sectional area of the shaft 1.42 kg / h cm 2 ) was.
[0151] The obtained resin kneaded product was cooled and coarsely pulverized using a pulverizer "Rotoplex" (manufactured by Hosokawa Micron Corporation), and a coarsely pulverized product with a volume median particle size of 2 mm or less was obtained using a sieve with a mesh size of 2 mm. The obtained coarsely pulverized product was finely pulverized using a DS2 type air classifier (impingement plate type, manufactured by Japan Pneumatic Co., Ltd.) by adjusting the pulverization pressure so that the volume median particle size was 6.5 μm. The obtained finely pulverized product was classified using a DSX2 type air classifier (manufactured by Japan Pneumatic Co., Ltd.) by adjusting the static pressure (internal pressure) so that the volume median particle size was 6.5 μm, and toner particles were obtained. 100 parts by mass of toner particles, 2.5 parts by mass of hydrophobic silica "RY50" (manufactured by Nippon Aerosil Co., Ltd., number average particle size: 0.04 μm), and 1.0 part by mass of hydrophobic silica "Cabosil (registered trademark) TS720" (manufactured by Cabot Japan Co., Ltd., number average particle size: 0.012 μm) were placed in a Henschel mixer, stirred, and passed through a 150 mesh sieve to obtain toner 8. The obtained toner was evaluated, and the results are shown in Table 6.
[0152] [Table 6]
[0153] [Resin manufacturing] [Production of amorphous resin] Production Example A2 (Production of Resin A-2) The inside of a 10 L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 3,253 g of a propylene oxide (2.2) adduct of bisphenol A, 1,003 g of terephthalic acid, 25 g of tin(II) di(2-ethylhexanoate), 2.5 g of 3,4,5-trihydroxybenzoic acid (gallic acid), and 394 g of hydrocarbon wax "Paracol 6490" (manufactured by Nippon Seiro Co., Ltd., acid value 18 mg KOH / g, hydroxyl value 97 mg KOH / g) were placed in the flask. The mixture was heated to 235°C with stirring under a nitrogen atmosphere and maintained at 235°C for 8 hours, and then the pressure in the flask was reduced and maintained at 8 kPa for 1 hour. After that, the pressure was returned to atmospheric pressure, and then the mixture was cooled to 160°C. While the mixture was kept at 160°C, a mixture of 2,139g of styrene, 535g of stearyl methacrylate, 107g of acrylic acid, and 321g of dibutyl peroxide was added dropwise over 3 hours. After that, the mixture was kept at 160°C for 30 minutes, and then heated to 200°C. The pressure in the flask was further reduced and kept at 8kPa for 1 hour. After that, the mixture was returned to atmospheric pressure, and then cooled to 190°C. 129g of fumaric acid, 94g of sebacic acid, 214g of trimellitic anhydride, and 2.5g of 4-tert-butylcatechol were added, and the temperature was raised to 210°C at 10°C / hr. Then, the reaction was continued at 4kPa until the desired softening point, and resin A-2 was obtained. The physical properties are shown in Table 7.
[0154] Manufacturing Example B2 (Manufacturing of Resin B-2) The inside of a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 3,265 g of ethylene oxide (2.2) adduct of bisphenol A, 1,334 g of terephthalic acid, 25 g of tin (II) di(2-ethylhexanoate), and 2.5 g of 3,4,5-trihydroxybenzoic acid (gallic acid) were added, and the temperature was raised to 235°C while stirring under a nitrogen atmosphere, and after maintaining at 235°C for 6 hours, the pressure in the flask was further reduced and maintained at 8.3 kPa for 1 hour. After that, the pressure was returned to atmospheric pressure, and the flask was cooled to 180°C, and 73 g of adipic acid, 135 g of dodecenylsuccinic anhydride, and 193 g of trimellitic anhydride were added, and the temperature was raised to 220°C at 10°C / hr, and then the pressure in the flask was reduced and the reaction was carried out at 10 kPa until the desired softening point, and resin B-2 was obtained. The physical properties are shown in Table 7.
[0155] [Table 7]
[0156] [Production of resin particle dispersion] Production Example X2 (Production of Resin Particle Dispersion X-2) 210 g of Resin A-2, 90 g of Resin C-1, and 360 g of methyl ethyl ketone were placed in a 3 L vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and the resins were dissolved at 73° C. for 2 hours. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization with respect to the acid value of the resin was 60 mol%, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C, 600 g of deionized water was added over 60 minutes while stirring at 280 r / min (circumferential speed 88 m / min) to cause phase inversion emulsification. While continuing to maintain the temperature at 73°C, methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion. Thereafter, while continuing to stir at 280 r / min (circumferential speed 88 m / min), the aqueous dispersion was cooled to 30°C, and deionized water was added so that the solid concentration was 20 mass%, thereby obtaining a resin particle dispersion X-2. The volume median particle diameter D of the obtained resin particles was 50 and CV values are shown in Table 8.
[0157] Production Example Y2 (Production of Resin Particle Dispersion Y-2) 300 g of Resin B-2 and 300 g of methyl ethyl ketone were placed in a 3 L vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and the resin was dissolved over 2 hours at 40° C. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization with respect to the acid value of the resin was 60 mol%, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 40°C, 600g of deionized water was added over 60 minutes while stirring at 280r / min (circumferential speed 88m / min) to cause phase inversion emulsification. The temperature was raised to 73°C, and methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion. Thereafter, the aqueous dispersion was cooled to 30°C while stirring at 280r / min (circumferential speed 88m / min), and deionized water was added so that the solid concentration was 20 mass%, to obtain resin particle dispersion Y-2. The volume median particle diameter D of the obtained resin particles was 50 and CV values are shown in Table 8.
[0158] [Table 8]
[0159] (Production of Colorant Dispersion) Manufacturing example Z21 In a 250 mL polyethylene bottle, 0.765 g (effective content 0.306 g) of the aqueous solution of the addition polymer E-1 obtained in Production Example E1 (solid content concentration 40%), 15 g of titanium oxide (CR-80 manufactured by Ishihara Sangyo Kaisha, Ltd., rutile type, alumina, silica treatment, average primary particle size 250 nm), 15.3 g of water were added, and 369 g of zirconia beads (diameter 2 mm) were added, and dispersion was performed for 8 hours at 25 ° C. using a benchtop pot mill stand (manufactured by AS ONE Corporation). The zirconia beads were removed using a mesh, and the solid content concentration was adjusted with water to obtain colorant dispersion liquid Z-21 (solid content concentration 30 mass %).
[0160] Manufacturing examples Z22~Z24 Colorant dispersions Z-22 to Z-24 (solid concentration 30% by mass) were obtained in the same manner as in Production Example Z21, except that the aqueous solution of addition polymer E-1 in Production Example Z21 was changed to the aqueous solutions of addition polymers E-2 to E-4 shown in Table 9, respectively.
[0161] Manufacturing example Z25 Colorant dispersion Z-25 (solid concentration 30% by mass) was obtained in the same manner as in Production Example Z21, except that the amount of the solution of addition polymer E-1 was changed to 0.379 g (effective content 0.152 g).
[0162] Manufacturing example Z26 Colorant dispersion Z-26 (solid concentration 30% by mass) was obtained in the same manner as in Production Example Z21, except that the amount of the solution of addition polymer E-1 was changed to 4.12 g (effective content 1.67 g).
[0163] Manufacturing example Z27 In a 250 mL polyethylene bottle, 2.04 g (active content 0.31 g) of 15 mass% sodium dodecylbenzenesulfonate aqueous solution "Neopelex G-15" (Kao Corporation, anionic surfactant, LAS), 15 g of titanium oxide (Ishihara Sangyo Kaisha, Ltd. CR-80, rutile type, alumina, silica treatment, average primary particle size 250 nm), 15.3 g of water were added, and 369 g of zirconia beads were added, and dispersion was performed for 8 hours at 25 ° C. using a benchtop pot mill stand (AS ONE Corporation). The zirconia beads were removed using a mesh, and the solid content was adjusted with water to obtain colorant dispersion liquid Z-27 (solid content concentration 30 mass %).
[0164] Manufacturing example Z28 In a 250 mL polyethylene bottle, 0.31 g of polyoxyethylene distyrenated phenyl ether "EMULGEN A-60" (Kao Corporation, nonionic surfactant), 15 g of titanium oxide (Ishihara Sangyo Kaisha, Ltd. CR-80, rutile type, alumina, silica treatment, average primary particle size 250 nm), 15.3 g of water were added, and 369 g of zirconia beads were added, and dispersion was performed for 8 hours at 25 ° C. using a benchtop pot mill stand (AS ONE Corporation). The zirconia beads were removed using a mesh, and the solid concentration was adjusted with water to obtain titanium oxide dispersion liquid Z-28 (solid concentration 30 mass %).
[0165] [Table 9]
[0166] [Toner manufacturing] Example 21 (Preparation of Toner 21) In a 3 L four-neck flask equipped with a dehydration tube, a stirrer and a thermocouple, 400 g of resin particle dispersion X-2, 39 g of release agent particle dispersion W-1, 39 g of release agent particle dispersion W-2, 136 g of colorant particle dispersion Z-21, 8 g of a 10 mass% aqueous solution of polyoxyethylene (50) lauryl ether "EMULGEN 150" (Kao Corporation, nonionic surfactant), and 5 g of a 15 mass% aqueous solution of sodium dodecylbenzenesulfonate "NEOPELEX G-15" (Kao Corporation, anionic surfactant) were mixed at a temperature of 25° C. Next, an aqueous solution in which 26 g of 4.8 mass% potassium hydroxide aqueous solution was added to an aqueous solution in which 40 g of ammonium sulfate was dissolved in 484 g of deionized water was added dropwise at 25° C. over 10 minutes while stirring the mixture, and then the temperature was raised to 62° C. over 2 hours to obtain the volume median particle diameter D of the aggregated particles. 50 The temperature was maintained at 62° C. until the particle diameter reached 5.6 μm, to obtain a dispersion of aggregated particles. The aggregated particle dispersion was cooled to 57° C., and while maintaining the temperature at 57° C., 60 g of resin particle dispersion Y-2 was added over 90 minutes to obtain an aggregated particle dispersion in which resin particles were aggregated to aggregated particles. To the obtained dispersion of aggregated particles, 211 g of sodium polyoxyethylene lauryl ether sulfate "EMAL E-27C" (manufactured by Kao Corporation, anionic surfactant, effective concentration 27% by mass) and 1372 g of deionized water were added. The temperature was then raised to 75°C over 1 hour, and the temperature was maintained at 75°C until the circularity reached 0.970, thereby obtaining a dispersion of fused particles in which the aggregated particles were fused together. The obtained dispersion of fused particles was cooled to 30° C., and the solid matter was separated by suction filtration, washed with deionized water at 25° C., and then vacuum dried at 30° C. for 48 hours to obtain toner particles. The physical properties of the obtained toner particles are shown in Table 10. 100 parts by mass of the toner particles, 2.5 parts by mass of hydrophobic silica "RY50" (manufactured by Nippon Aerosil Co., Ltd., number average particle size: 0.04 μm), and 1.0 part by mass of hydrophobic silica "Cabosil (registered trademark) TS720" (manufactured by Cabot Japan Co., Ltd., number average particle size: 0.012 μm) were placed in a Henschel mixer, stirred, and passed through a 150 mesh sieve to obtain toner 1. The obtained toner was evaluated, and the results are shown in Table 10.
[0167] Examples 22 to 27, Comparative Examples 21 to 23 (Preparation of toners 22 to 30) A toner was prepared in the same manner as in Example 21, except that the types of resin particle dispersion liquid and colorant particle dispersion liquid used were changed as shown in Table 10. The physical properties of the obtained toner particles and the evaluation results of the toner are shown in Table 10. In Example 24, the amount of colorant dispersion used was changed to 272 g, in Example 25, the amount of colorant dispersion used was changed to 95 g, in Example 26, the amount of colorant dispersion used was changed to 136 g, and in Example 27, the amount of colorant dispersion used was changed to 148 g.
[0168] [Table 10]
[0169] From the results of the Examples and Comparative Examples described above, it is clear that the white toner for developing electrostatic images of the present invention is a toner capable of obtaining white images with excellent concealing properties. It has also been shown that the toner of the present invention has the effects of being excellent in low-temperature fixing property and charging property.
Claims
1. A white toner for developing electrostatic images, comprising a binder resin and a colorant, the binder resin contains an amorphous polyester resin and a crystalline polyester resin, the colorant is titanium oxide coated with an addition polymer of raw material monomers including an addition polymerizable monomer having an anionic group and an addition polymerizable monomer having a polyalkylene oxide group, The content of the hydrophobic monomer in the raw material monomer is 0% by mass or more and 5% by mass or less. White toner for developing electrostatic images.
2. 2. The white toner for developing electrostatic images according to claim 1, wherein a mass ratio of titanium oxide to the addition polymer in the colorant (titanium oxide / addition polymer) is 50 / 50 or more and 99.5 / 0.5 or less.
3. 3. The white toner for developing electrostatic images according to claim 1, wherein the addition polymerizable monomer having an anionic group is at least one selected from the group consisting of acrylic acid and methacrylic acid.
4. 4. The white toner for developing electrostatic images according to claim 1, wherein a mass ratio of the addition polymerizable monomer having an anionic group to the addition polymerizable monomer having a polyalkylene oxide group (addition polymerizable monomer having an anionic group / addition polymerizable monomer having a polyalkylene oxide group) in the raw material monomers is 5 / 95 or more and 50 / 50 or less.
5. 5. The white toner for developing electrostatic images according to claim 1, wherein the average primary particle diameter of the titanium oxide is from 220 nm to 390 nm.
6. 6. The white toner for developing electrostatic images according to claim 1, wherein the content of titanium oxide in the toner is from 10% by mass to 60% by mass.
Citation Information
Patent Citations
Method for manufacturing white toner
JP2003255606A
Toner and method for manufacturing toner
JP2005031512A
Toner for electrostatic image development, developer for electrostatic image development and image forming method
JP2007033719A
White pigment, electrostatic charge image developing toner and method for producing white pigment
JP2017122185A
White toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
JP2019113686A